2014
DOI: 10.1073/pnas.1411253111
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinting, action, and interaction of maternal and fetal genomes

Abstract: Mammalian viviparity (intrauterine development of the fetus) introduced a new dimension to brain development, with the fetal hypothalamus and fetal placenta developing at a time when the fetal placenta engages hypothalamic structures of the maternal generation. Such transgenerational interactions provide a basis for ensuring optimal maternalism in the next generation. This success has depended on genomic imprinting and a biased role of the matriline. Maternal methylation imprints determine parent of origin exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 70 publications
0
40
0
Order By: Relevance
“…23,24 In addition, a number of GWAS have identified genetic variation at or near imprinted genes associated with autism and other mental deficits. 13 Importantly, the placenta and brain are the 2 organs that have the most active imprinted genome because both organs are under tremendous selective pressure to optimize growth and development, and both are thought to have undergone co-adaptation, leading to co-expression of many of the same imprinted genes. 13,25 Although the expression of imprinted genes is highly regulated, our group and others have demonstrated subtle variation in the expression of these genes in the placenta of healthy newborns 15,26,27 ; yet, little is known about the relationships between this variation in expression and newborn and childhood outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…23,24 In addition, a number of GWAS have identified genetic variation at or near imprinted genes associated with autism and other mental deficits. 13 Importantly, the placenta and brain are the 2 organs that have the most active imprinted genome because both organs are under tremendous selective pressure to optimize growth and development, and both are thought to have undergone co-adaptation, leading to co-expression of many of the same imprinted genes. 13,25 Although the expression of imprinted genes is highly regulated, our group and others have demonstrated subtle variation in the expression of these genes in the placenta of healthy newborns 15,26,27 ; yet, little is known about the relationships between this variation in expression and newborn and childhood outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…13 Importantly, the placenta and brain are the 2 organs that have the most active imprinted genome because both organs are under tremendous selective pressure to optimize growth and development, and both are thought to have undergone co-adaptation, leading to co-expression of many of the same imprinted genes. 13,25 Although the expression of imprinted genes is highly regulated, our group and others have demonstrated subtle variation in the expression of these genes in the placenta of healthy newborns 15,26,27 ; yet, little is known about the relationships between this variation in expression and newborn and childhood outcomes. We demonstrated that infants with specific, coordinated profiles of expression of subset of imprinted genes in the placenta were at increased risk for sub-optimal performance on measures of movement quality and for exhibiting an elevated number of signs of physiologic stress of abstinence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of NGS has made it possible to identify the precise positions of epigenetic modification . More and more studies are reporting on the role of epigenetic mechanisms in embryogenesis, cell differentiation, genome imprinting, inactivation of X chromosomes and ageing …”
Section: Beginning Of Epigeneticsmentioning
confidence: 99%
“…Thus, at the Sackler Colloquium mechanisms discussed were those for maternal behaviors (13), sexual behaviors and stress (14), and hypothalamically controlled behaviors (15). Circadian-regulated behaviors (16) clearly represent a case of normal behaviors epigenetically regulated, whereas problematic and abnormal behaviors, such as in Prader-Willi syndrome (17), and changes in behavior during aging were also discussed.…”
mentioning
confidence: 99%